Spatially resolved X-ray study of the mixed morphology SNR G359.1-0.5. Issue 4 (23rd February 2022) - Eppens, L K; Albacete Colombo, J F; Combi, J A; Reynoso, E M
ABSTRACT: We present a detailed spatially resolved X-ray study of Chandra observations towards the central region of the supernova remnant (SNR) G359.1-0.5. We removed 168 point-like sources and performed an adaptive smoothing on the entire field-of-view of the Chandra ACIS-I observation. The images obtained show an extended X-ray emission below 4.0 keV that partially fills the interior of G359.1-0.5. In order to characterize the X-ray emission, we divide the emitting area into 10 different regions inside the remnant. We identify the presence of at least four emission lines that confirm the thin thermal plasma origin. All spectral regions are well fitted by a recombining plasma model (VRNEI) with an absorbing column density range from 1.5 to 2.1× 10^22 cm^-2, and electron temperatures from 0.14 to 0.19 keV . We also calculated an average electron density of 0.7 cm^-3, estimated an age of 2.8 × 10 4 yr for the remnant, which can be lower if the filling factor is considered, and an X-ray luminosity of 1.6 × 10^35 erg s^-1 . Finally, we show that the X-ray emission is morphologically anti-correlated with adjacent CO clouds interacting with the SNR. Our results favour that the recombining plasma inside G359.1-0.5 could be explained via adiabatic cooling.